A prospective analysis of factors associated with decreased physical activity in patients with cirrhosis undergoing transplant evaluation. (18th September 2015) - Dela Cruz, Anna Christina; Vilchez, Valery; Kim, Sooyeon; Barnes, Benjamin; Ravinuthala, Abhishek; Zanni, Anthony; Galuppo, Roberto; Sourianarayanane, Achuthan; Patel, Trushar; Maynard, Erin; Shah, Malay B.; Daily, Michael F.; et al.
Abstract: Background: Physical activity (PA) has been associated with improved recovery time after transplantation. Handgrip strength has been related to post‐transplant outcomes. Aim: To evaluate predictors of PA and grip strength in patients with cirrhosis undergoing liver transplant evaluation. Methods: Single‐center, prospective analysis. Results: One hundred patients were evaluated (54% male, mean age 53 ± 9). Common etiologies of liver disease were non‐alcoholic steatohepatitis (27%), hepatitis C (22%) and alcoholic liver disease (21%). Mean model of end‐stage liver disease (MELD) score was 13.5. Forty‐one percent had a history of smoking. Ninety‐three patients completed the International Physical Activity Questionnaire (IPAQ). The median total PA score was 33 metabolic equivalent (MET)‐min/wk. The mean total grip strength was 62.1 ± 22 lb. Total grip strength was found to be an independent predictor of low–moderate PA (OR 4.7, 95% CI 1.4–16.2, p = 0.038), and smoking was the only significant factor associated with reduced grip strength (OR 3.4, 95% CI 1.4–8, p = 0.005). Conclusions: Patients with end‐stage liver disease undergoing liver transplant evaluation have reduced total PA by IPAQ. Total grip strength was found to be a significant predictor of low–moderate PA in patients with cirrhosis. Smoking is a risk factor for reduced grip strength, an important indicator of muscle wasting in cirrhotics.